Mongolian spot. Incidence and natural history in western Sicily. - Maniscalco, M.; Noto, G.; Zichichi, L.; Rinaldi, R.; Milano, A.; Patrizi, A. (European Journal of Pediatric Dermatology, 2004)
The prevalence of Mongolian spot was investigated in 736 children (339 males) of western Sicily. Its prevalence was 13.3%, 13.9% in males, 12.8% in females, thus higher than that reported in the Caucasian race. Mongolian spot most frequently affected the sacrococcigeal area, followed by the buttocks and lumbar region. In 3.1% of cases it affected other sites. As reported in the relevant literature, Mongolian spot was stable in the first two years and later on slowly faded. It eventually regressed in almost all the subject of thestudy within 6 years.